Changes in Purchasing Behaviour after the Onset of the COVID-19 Pandemic Related to the Application of Corporate Social Responsibility - Ušák, Peter; Bednárik, Jaroslav (Communication Today, 2022)
The issue of social responsibility is getting more and more attention nowadays. In connection with the onset of the COVID-19 pandemic, we identified that consumers began to prefer the purchase of products whose production and consumption are socially responsible over products not meeting these characteristics. Our research shows that companies have experienced this behaviour and perceive the application of CSR principles as a competitive advantage. The study focuses on changes in consumer purchase behaviour in terms of social responsibility during the COVID-19 pandemic. The study aims to identify how the corona crisis has affected consumers’ purchase behaviour concerning social responsibility and to point out that adhering to the principles of social responsibility means increasing competitiveness for businesses in a market environment. To achieve the goal, we conducted a survey of the primary issue as a questionnaire in July 2021 and August 2021, with a quantitative and qualitative evaluation of responses obtained from respondents. The results suggest that marketing communication plays a significant role in applying the principles of social responsibility and, at the same time, comes along with a competitive advantage.